Public Leadership, Rules and Legal Values: Realizing Good Governance in the Era of Transparency - Herijanto Bekti (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze the role of public leadership, regulations, and legal values ​​in realizing good governance in the era of transparency. The implementation of good governance principles requires public leaders with integrity, a clear regulatory system, and legal values ​​that ensure justice, accountability, and openness in governance. Using a descriptive qualitative approach, this study explores the relationship between responsive and participatory public leadership and the effectiveness of regulatory implementation and the internalization of legal values ​​in bureaucratic practices. The results demonstrate that the synergy between public leadership, legal regulations, and legal values ​​plays a significant role in realizing good governance in the era of transparency. Public leadership with integrity has proven to be a key driver of a culture of openness within the bureaucracy, while legal regulations provide a framework of certainty and accountability that strengthens the implementation of transparency. Furthermore, legal values ​​ensure that the practice of openness does not stop at procedural compliance but is carried out with a strong moral commitment. These three aspects, when integrated, create a governance mechanism that is more open, trustworthy, and responsive to public needs, thereby improving the overall quality of public services